2000
DOI: 10.21273/jashs.125.4.436
|View full text |Cite
|
Sign up to set email alerts
|

Day and Night Temperatures, Daily Light Integral, and CO2 Enrichment Affect Growth and Flower Development of Pansy (Viola ×wittrockiana)

Abstract: Pansy [Viola ×wittrockiana Gams. `Delta Yellow Blotch' (Yellow) and `Delta Primrose Blotch' (Primrose)] plants were grown in a greenhouse under two CO2 concentrations [ambient (≈400 μmol·mol-1) and enriched (≈600 μmol·mol-1)], three daily light integrals (DLI; 4.1, 10.6, and 15.6 mol·m-2·d-1), and nine combinations of day and night temperatures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
6
31
0
Order By: Relevance
“…Flowering time of dahlia, French marigold, and zinnia (Year 2 only) was similar among temperature treatments with the same MDT. This response reinforces the paradigm that flowering rate is a function of the MDT and, within limits, the effects of day and night temperature on progress toward flowering are equal (Niu et al, 2000;Summerfield et al, 1991). Our results are in agreement with those of Mortensen and Moe (1992), who reported no difference in flowering time of fuchsia (Fuchsia ·hybrida hort.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Flowering time of dahlia, French marigold, and zinnia (Year 2 only) was similar among temperature treatments with the same MDT. This response reinforces the paradigm that flowering rate is a function of the MDT and, within limits, the effects of day and night temperature on progress toward flowering are equal (Niu et al, 2000;Summerfield et al, 1991). Our results are in agreement with those of Mortensen and Moe (1992), who reported no difference in flowering time of fuchsia (Fuchsia ·hybrida hort.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with Myster and Moe's (1995) findings that the relative promotion or suppression of stem elongation is influenced by the magnitude of DIF. Similar effects of DIF on plant height have been reported in other bedding plants, including geranium (Mortensen and Moe, 1992), pinnate dahlia (Brøndum and Heins, 1993), impatiens (Mortensen and Moe, 1992), pansy (Niu et al, 2000), petunia (Kaczperski et al, 1991), red salvia (Mortensen and Moe, 1992), snapdragon (Antirrhinum majus L.; Neily et al, 1997), and zinnia (Neily et al, 1997). For example, stem elongation during the vegetative stage in snapdragon and zinnia increased by 38% and 13%, respectively as DIF (13-h day/11-h night) increased from -5 to +5°C (Neily et al, 1997).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…For example, White and Warrington (1984) observed an increase in geranium plant dry mass from 2.9 to 3.4 g as the DLI increased from 6.5 to 19.4 mol·m -2 ·d -1 , while the leaf area per plant decreased from 1047 to 820 cm 2 as DLI increased from 8.7 to 20.5 mol·m -2 ·d -1 . Niu et al (2000) reported that the dry mass of pansy 'Delta Yellow Blotch' increased by 40% as the DLI increased from 4.1 to 10.6 mol·m -2 ·d -1 . Kaczperski et al (1991) reported that petunias grown at 6.5 mol·m -2 ·d -1 were up to 6 cm taller than plants grown under 13.0 mol·m -2 ·d -1 .…”
mentioning
confidence: 99%